Pelatihan dan Pendampingan Media Loose Part untuk Membangun Keterampilan Abad 21 Guru-guru PAUD: Loose Part Media Training and Assistance to Build 21st Century Skills for PAUD Teachers - Suci Frisnoiry; Tiur Malasari Siregar; Elfitra Elfitra; Sara Frimaulia (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The partner who is the subject of this service program is RA Al-Amin. RA Al-Amin is a kindergarten located on Jalan Haji Muhammad Yamin No.482, Pahlawan, Medan Perjuangan, Sei Kera Hulu, Kec. Medan Perjuangan, Medan City, North Sumatra. RA Al-Amin is in the same yard as the AL-Amin Mosque. The Pk Mini program was carried out to build the 21st-century skills of RA AL-Amin teachers. This is done based on an analysis of the problems experienced by partners: the teacher's experience in participating in training related to media development is low, learning is monotonous, media availability is very lacking, media availability is very lacking, media that available are less effective, and the playing field is inadequate. The solutions offered are based on partner problems: organizing Loose Part media training for RA Al-Amin teachers, organizing assistance in making and using Loose Part media for RA Al-Amin teachers, and providing Loose Part media Part to RA Al-Amin. The results of this service found that teachers have skills in managing learning to the demands of the 21st century and can effectively organize learning using Loose Part media.